Endothelin receptor antagonists alleviate blood-brain barrier disruption and cerebral edema in a mouse model of traumatic brain injury: A comparison between bosentan and ambrisentan. (15th September 2020) - Michinaga, Shotaro; Inoue, Anna; Yamamoto, Hayato; Ryu, Ryotaro; Inoue, Ayana; Mizuguchi, Hiroyuki; Koyama, Yutaka
Abstract: Traumatic brain injury (TBI) is induced by the immediate physical disruption of brain tissue. TBI causes disruption of the blood–brain barrier (BBB) and brain edema. In the cerebrospinal fluid (CSF) of TBI patients, endothelin-1 (ET-1) is increased, suggesting that ET-1 aggravates TBI-induced brain damage. In this study, the effect of bosentan (ETA /ETB antagonist) and ambrisentan (ETA antagonist) on BBB dysfunction and brain edema were examined in a mouse model of TBI using lateral fluid percussion injury (FPI). FPI to the mouse cerebrum increased the expression levels of ET-1 and ETB receptors. Administration of bosentan (3 or 15 mg/kg/day) and ambrisentan (0.1 or 0.5 mg/kg/day) at 6 and 24 h after FPI ameliorated BBB disruption and cerebral brain edema. Delayed administration of bosentan from 2 days after FPI also reduced BBB disruption and brain edema, while ambrisentan had no significant effects. FPI-induced expression levels of ET-1 and ETB receptors were reduced by bosentan, but not by ambrisentan. In cultured mouse astrocytes and brain microvessel endothelial cells, ET-1 (100 nM) increased prepro--ET-1 mRNA, which was inhibited by bosentan, but not by ambrisentan. FPI-induced alterations of the expression levels of matrix metalloproteinase-9, vascular endothelial growth factor-A, and angiopoietin-1 in the mouse cerebrum were reduced by delayed administration of bosentan, while ambrisentan had no significant effects. These results suggest that ET antagonists are effective in improving BBB disruption and cerebral edema in TBI patients and that an ETA /ETB non-selective type of antagonists is more effective. Graphical abstract: Image 1 Highlights: Administrations of bosentan and ambrisentan immediate after FPI protect BBB in mouse cerebrum. Delayed bosentan administration, but not ambrisentan, recovers BBB in a mouse FPI model. Bosentan reduces TBI-induced increases in ET-1 and ETB receptors expression. The present findings may suggest effectiveness of bosentan and ambrisentan for TBI.